Critical Analysis on the Essence of Muá¸Ärabah and MushÄrakah and Its Relation to á¸ŒamÄn (Malaysian Management Journal, 2019)
The study aims to explore the permissibility of guarantee for muá¸Ärabah and mushÄrakah based contracts and to discuss in detail the essence of muá¸Ärabah and mushÄrakah, which both contracts contain the concepts of trust and profit sharing. The study conducted the qualitative research approaches which consist of documents analysis, interviews and observations in few phases. The study found that there are few matters that can be listed as genuine essence of muá¸Ärabah and mushÄrakah. It also found that the majority of scholars were of the view of prohibiting capital guarantee by partners. It also proved that few statements such as Ibn Taymiyahâ€™s statement were quoted out of context and definitely not appropriate to attribute the stance of those who allowed capital guarantee to him by using his statements, as those statements showed something else. However, a third party may undertake to bear the loss of capital due to misconduct or negligence on the part of the manager for both contracts. The rabb al-mÄl (capital provider) may also take collateral from the muá¸Ärib, provided that the collateral can only be liquidated in the event of negligence or misconduct or violation of contractual terms by the muá¸Ärib.